Pengaruh Support Educative dengan Media Audio Visual Terhadap Self Care Management pada Hipertensi - Karina Anjelita; Kris Linggardini (Malahayati Nursing Journal, 2025)
ABSTRACT Inadequate self-care management among hypertensive patients can result in increased risks of complications and prolonged treatment durations. To address this issue, providing educative support through audio-visual media focused on hypertension management is crucial to enhancing health outcomes for residents of the Sudagaran Elderly Social Service Center. This study aims to evaluate the effect of educative support using audio-visual media on improving self-care management among hypertensive patients at the Sudagaran Elderly Social Service Center. Quantitative research approach was adopted, employing a pre-experimental design with a one-group pretest-posttest method. The study was conducted over 30 days at the Sudagaran Elderly Social Service Center, involving 30 purposively selected participants. Data were analyzed using the Paired Sample T-test to assess the intervention's effectiveness . The findings revealed a significant improvement in self-care management among hypertensive patients following the implementation of educative support using audiovisual media. The effect size calculation indicated a substantial impact, with r=0.95.  This study demonstrates that educative support delivered through audiovisual media has a profound positive effect on self-care management in hypertensive patients at the Sudagaran Elderly Social Service Center. Keywords: Self-Care Management, Educative Support, Audio Visual Media, Hypertension, Elderly care.  ABSTRAK Kurangnya praktik self care management pada penderita hipertensi dapat berdampak pada peningkatan komplikasi dan perawatan yang lebih lama. Oleh karena itu dibutuhkannya memberikan support educative dengan media audio visual tentang kesehatan hipertensi untuk mengoptimalkan kesehatan yang lebih baik di PPSLU Sudagaran. Mengetahui pengaruh support educative dengan media audio visual terhadap self care management pada pasien hipertensi di Panti Pelayanan Sosial Lanjut Usia Sudagaran. Penelitian kuantitatif dengan desain pre-experimental dengan one grup pretest-posttest. Penelitian dilakukan selama 30 hari di Panti Pelayanan Sosial Lanjut Usia Sudagaran. Sampel berjumlah 30 orang yang dipilih secara purposive sampling. Analisis data menggunakan uji Paired Simple T-test. Hasil penelitian menunjukkan pemberian support educative dengan media audio visual berpengaruh besar terhadap peningkatan self care management pada pasien hipertensi di Panti Pelayanan Sosial Lanjut Usia Sudagaran. Dengan hasil perhitungan effect size r = 0,95. Dari penelitian ini dapat disimpulkan bahwa terdapat pengaruh support educative dengan media audio visual terhadap self care management pada pasien hipertensi di Panti Pelayanan Sosial Lanjut Usia Sudagaran. Kata Kunci: Self-Care Management, Educative Support, Audio-Visual Media, Hypertension, Elderly Care.